2017
DOI: 10.3342/kjorl-hns.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Outcome of Cochlear Implantation in Adolescent and Adult Patients with Enlarged Vestibular Aqueduct and Biallelic SLC26A4 Mutations

Abstract: Background and ObjectivesZZMutations of the SLC26A4 gene cause congenital hearing loss and enlarged vestibular aqueduct (EVA). A considerable proportion of patients with SL-C26A4 mutations have significant residual hearing at birth that eventually worsen and become the cause for cochlear implantation (CI) later in their adolescence or adulthood. We analyzed the auditory outcome and prognostic factors of CI in patients with EVA and biallelic SLC26A4 mutations showing progressive early-onset hearing loss, who ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 7 Study had shown that the auditory outcome for patients with LVAS following cochlear implantation was comparable to those without any inner ear abnormality. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Study had shown that the auditory outcome for patients with LVAS following cochlear implantation was comparable to those without any inner ear abnormality. 8 …”
Section: Discussionmentioning
confidence: 99%